Choipan Isi Daun Genjer dan Ebi Cincang dengan Saus Cabai di Kazuki Resto Cipadung Ujung Berung Bandung - Mayang Parameswari; Ida Hafidah (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Kazuki Resto is an Eastern-themed café and restaurant located at Jl. Raya A.H Nasution No. 39A, Bandung, open from 11:00 AM to 11:00 PM. To diversify the menu, the author introduces choipan, a Chinese snack made from genjer leaves (Limnocharis flava) and minced shrimp. The term